Forensic interventions for therapy and rehabilitation : case studies and analysis - Winder, Belinda (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Forensic Interventions for Therapy and Rehabilitation: Case Studies and Analysis provides an up-to-date overview of the latest therapeutic ideas being used for forensic service users and prisoners in both custodial and community settings. The field of forensic work is increasingly being recognised for its importance, both in terms of the value of the work in reducing reoffending but also in terms of the salience given to it by the media, the public and politically. This text reflects current policy and practice, and furthermore considers the therapeutic encounter from a broad perspective which incorporates individual, group and systemic interventions. Forensic Interventions for Therapy and Rehabilitation includes chapters on a range of therapeutic models, issues pertinent to specific groups of people with criminal convictions, as well as discussion on the various contexts in which interventions take place. Forensic Interventions for Therapy and Rehabilitation is essential reading for all students of forensic or clinical psychology, as well as practitioners in the field"--
Keywords: Forensic psychology; Prison psychology; PSYCHOLOGY / General; PSYCHOLOGY / Applied Psychology